2013
DOI: 10.1186/1476-4598-12-80
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumor necrosis factor-alpha promoter variants with risk of HPV-associated oral squamous cell carcinoma

Abstract: BackgroundTumor necrosis factor alpha (TNF-α) plays an important role in inflammation, immunity, and defense against infection and clearance of human papillomavirus (HPV). Thus, genetic variants may modulate individual susceptibility to HPV-associated oral squamous cell carcinoma (OSCC).MethodsIn this study we genotyped four common single nucleotide polymorphisms (SNPs) in the TNF-α promoter [ −308G > A(rs1800629), -857C > T (rs1799724), -863C > A (rs1800630), and -1031T > C (rs1799964)] and determined HPV16 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 28 publications
3
24
0
7
Order By: Relevance
“…Polymorphisms in human IL-1b and TNF-a genes have also been reported to influence cytokine expression [54]. TNF-a can directly control HPV infection by induction of apoptosis in HPV-infected cells, such as cervical cancer cells [55 ]. The perturbation of the balance between proand anti-inflammatory cytokine levels can be caused by inherited gene mutations, from which common genetic variants can also alter the expression or function of key genes, disrupting the balance of cytokines, and thus affecting cancer risk and outcome.…”
Section: Polymorphisms Of Inflammatory and Immune Response Genes And mentioning
confidence: 97%
“…Polymorphisms in human IL-1b and TNF-a genes have also been reported to influence cytokine expression [54]. TNF-a can directly control HPV infection by induction of apoptosis in HPV-infected cells, such as cervical cancer cells [55 ]. The perturbation of the balance between proand anti-inflammatory cytokine levels can be caused by inherited gene mutations, from which common genetic variants can also alter the expression or function of key genes, disrupting the balance of cytokines, and thus affecting cancer risk and outcome.…”
Section: Polymorphisms Of Inflammatory and Immune Response Genes And mentioning
confidence: 97%
“…Supporting this are findings from multiple studies linking polymorphisms in immune mediators to an increased risk of cervical cancer . For HPV‐associated oropharyngeal cancer, polymorphisms in immune mediators, such as transforming growth factor‐beta1 and tumor necrosis factor‐alpha, as well as pathways critical to genome integrity and programmed cell death, such as p53 and p73, are linked to an increased risk of oropharyngeal cancer …”
Section: Discussionmentioning
confidence: 86%
“…Among the TNF-α-308 G/A and -857 C/T SNPs evaluated in this study, only TNF-α-857 C/T was found to be associated with gastric cancer. Several studies have reported the same association [9,20,[40][41][42][43], but studies attempting to associate cytokine expression with the presence of SNPs are uncommon [7].…”
Section: Discussionmentioning
confidence: 92%